2nd International Congress on Energy Efficiency and Energy Related Materials (ENEFM2014): Proceedings, Oludeniz, Fethiye/Mugla, Turkey, October 16-19, 2014 - Ducrotoy, Jean-Paul (Springer, 2016)
The proceedings of the 2nd International Congress on Energy Efficiency and Energy Related Materials include 73 peer-reviewed technical papers, submitted by leading academic and research institutions from over 20 countries and representing some of the most cutting-edge research available. The 73 papers are grouped into the following sections: